A microfluidic device for digital manipulation of gaseous samples. Issue 7 (11th March 2020) - Enel, A.; Bourrelier, A.; Vial, J.; Thiébaut, D.; Bourlon, B.
Abstract : The first device for digital manipulation of gaseous samples; from elementary operations to demonstration of a more complex application. Abstract : Digital microfluidics is known for fine manipulation of sub-millimeter samples, with applications from biological sample preparation to diagnostic testing. Unfortunately, until now, it has been only limited to liquid phases. In this paper, we present a new system based on a digital microfluidic platform (DMFP), which is able to digitally manipulate gaseous samples, such as alkanes from n -hexane to n -nonane. The DMFP relies mostly on interconnected micropreconcentrators (μPCs) to trap and release the samples depending on their controlled temperature. We show that the DMFP is capable of performing all basic operations of digital microfluidics: trapping/releasing and moving samples, adding samples and separating samples. As a first example of a more complex programmable use of our DMFP, we measured the breakthrough volume of alkanes on a Tenax TA adsorbent. The results were consistent with tabulated values obtained with standard laboratory instruments. This DMFP promises great possibilities for more complex programmable gas microfluidics digital devices and the development of new digital gas sample preparation and analysis methods.